PENGEMBANGAN KOSAKATA BAHASA INDONESIA - Karmaeni, Riyanto (Kementerian Sekretariat Negara Republik Indonesia, 2025)
Indonesian language, rooted from Malay language, has been continuously expanding. One of its expansions is shown from the increasing Indonesian vocabularies, from 23,000 words in 1953, increased to 91,000 words in 2015, and 120,468 words in 2023. Currently, the Pasti (Padanan Istilah) application consists of 169,059 terms from 48 domains. However, this number of vocabularies is still very limited if we compare to English vocabularies, which amounts to more than 1 million words. Therefore, we need to enhance Indonesian vocabularies by absorbing words from local and foreign languages. The purpose of this research is to develop Indonesian vocabularies so the users can easily express their ideas. The research methods used are 1) exploring the vocabulary from local languages in Indonesia and 2) developing acronym words. Based on the study, it is found that there are foreign words with inefficient equivalents, words which need to be created, possessive pronouns which need to be created, and phrases which can be used as words. Based on the results of the study, 40 neologisms are developed, namely: blero, solet, belat, bukel, modulel, tacap, tavis, tadik, barmas, parmas, rancikom, pilkirting, pilkirren, ka, da, madang, madlam, ceriyat, kabis, bukabis, bilat, bili, bicah, bijil, binap, bipos, bineg, bikha, bikhanol, bikhalog, bisikba, silmaan, mangun, gakima, gasima, dikel, sebel, sikba, natur, dan konni.